Wrestling with Nature: Scientists and the Others - Pavlas, Petr (Teorie vědy / Theory of Science, 2013)
Review: Peter HARRISON - Ronald L. NUMBERS - Michael H. SHANK (eds.) Wrestling with Nature: From Omens to Science. Chicago: Univer- sity of Chicago Press 2011, 416 s.